KEMAMPUAN MEMAHAMI KATA PADA ANAK PENDERITA DYSLEXIA DENGAN BANTUAN MEDIA GAMBAR - Novianti, Uria; Saman, Sisilya; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ The purpose of this research was to give contribution for knowledge development, especially in reading aspect and to detect the symptom of child with Dyslexia. This research use descriptive method. The form of research was qualitative. The research data was pronouncing words, understanding the meanings, mentioning the function of words on six years old child with Dyslexia in SLB Dharma Asih in reading using pictures. Subject of this research is a child with Dyslexia named Khairil Ramadhani. The research techniques were observation and documentation. The research results were: 1) mispronouncing on child with Dyslexia is subject of research can not remember letters which is similar, hard to remember letters in last position, if the letter is combined with the others, there will be a repeating, hard to concentrate and to remember for long; 2) misunderstanding meaning is the difficulty to spell and read if it is not helped with pictures. Subject of research sometimes found the difficulty to distinguish pictures that is given to him because in his mind it is different with given picture. Subject of research is used to pronouncing name for things with repeating and it has become a concept for him. Subject of research can not describe word picture that is given to him; 3) false in mentioning the functions of noun is cannot mention name for things specifically but generally. Subject of research can not describe functions of things detailed yet he can mention the function simply. The research results are expected to be useful to detect symptom of child with Dyslexia earlier in order to get teaching and education more intensive and continuous. Key words: Dyslexia, Pictures, Reading Ability, Six Years Old, Word.Â Â